"Detached concern" of medical students in a cadaver dissection course: A phenomenological study. Issue 3 (20th November 2015) - Tseng, Wei‐Ting; Lin, Ya‐Ping
Abstract : The cadaver dissection course remains a time‐honored tradition in medical education, partly because of its importance in cultivating professional attitudes in students. This study aims to investigate students' attitudes—specifically characterized as "detached concern"—in a cadaver dissection course. An interpretative phenomenological analysis was performed with semi‐structured, focus group interviews among 12 third‐year medical students from a Taiwanese medical school to reveal their perceptions and learning experiences regarding human cadaver dissection. Based on these interviews, four relevant categories of perspectives were delineated: (1) initial emotional impact, (2) human referents, (3) coping strategies, and (4) ways of perceiving cadavers. Students were divided into two groups based on these categories. Students in Group 1 developed mechanisms described as "detachment" to cope with their initial emotional reactions to cadaveric dissection, which was noted to have disruptive effects on their learning. They considered human referents to be learning obstacles and avoided contact with or thinking about the human referents while performing dissections. Some of them faced a conflict between perceiving the cadaver as a learning tool versus as a human being. This impasse could be resolved if they latently adopted a "perspective switch" between the concept of a learning tool (rational aspect) and a human being (sensitive aspect). The students in Group 2 had no obvious initial emotional reaction. For them, the human referents functioned as learning supports, and the cadavers were consistently perceived as humans. These students held the notion that "cadaver dissection is an act of love"; therefore, they did not experience any need to detach themselves from their feelings during dissection. This alternative attitude revealed that detached concern alone is not sufficient to describe the entire range of medical students' attitudes toward cadaver dissection. Anat Sci Educ 9: 265–271. © 2015 American Association of Anatomists.